The Function Of Derivational Affixes In Novel The Hobbit - Ida Bagus Gde Nova Winarta; I Dewa Ayu Devi Maharani Santika; Alvie Amin Rachmadi (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
When the students are able to identify derivational affix, they can develop their vocabulary because from just one word it can gain many words with different part of speech. Novel is a long essay in prose and contains a series of human life stories with others around them with accentuate the character and nature of the actor. In The Hobbit, the story inspired by a children fantasy. From having seeing such phenomenon, the writer found that mastering English is not easy if the students are lack of vocabulary. This research aimed to find out the derivational affixes in in in The Hobbit by J.R.R Tolkien novel. This research is descriptive qualitative research where researcher tries to find out the derivational affix and the roots from the words in The Hobbit by J.R.R Tolkien novel without using statistical calculation. In this research the writer uses all of words that are attached prefix and suffix as the data. The data source is all the chapters which are the beginning of the story, rising the case and the solution in The Hobbit by J.R.R Tolkien novel. The result of analyzing data was gained the derivational affixes that found in in The Hobbit by J.R.R Tolkien novel showed words are 100 (derivational suffixes).Then the roots from the words that also found are 27 (adjective derived from verb), 49 (noun derived from verb), 3 (verb derived from noun) and adverb derived from adjective (21) Keywords: Function of Derivational Affixes, novel, root, base